Carbon finance and funding for forest sector climate solutions: a review and synthesis of the principles, policies, and practices - Zhou, Kai; Midkiff, David; Yin, Runsheng; Zhang, Han (Frontiers in Environmental Science, 2024)
The question of funding necessary climate actions, including those in the forest sector, to drastically reduce greenhouse gas (GHG) emissions and global warming, is important to both national governments and international agencies. The objective of this paper is to address this question by reviewing and synthesizing the economic principles associated with reducing GHG emissions, the pricing mechanisms used to achieve that goal, and the diverse practices of climate finance. Included in the carbon pricing mechanisms and practices are carbon tax, compliance and voluntary emission trading, internal pricing, and funding via issuing bonds or mobilizing public budgetary resources. Then, it proceeds to describe the roles that public and private organizations can play and have played in supporting emission reduction and removal, which serves as a vital backdrop for examining current states and relative costs of forest sector initiatives. Overall, as reported by the World Bank, only about 23% of global GHG emissions are subject to any explicit price, and 75% of the emissions that are subject to a price are charged less than $10 per tCO2e. Market-based forest finance and international support for reducing emissions from deforestation and forest degradation have accounted for a small fraction of the total spent on climate mitigation and adaptation. Further, the more recent developments in carbon pricing and funding remain slow and disappointing. Without the right scale of green finance at the right time, however, it will be difficult to achieve the needed energy and economic transformation.